Contemporary Approaches to the Treatment of Acute Gastroenteritis in Children - Artem A. Ivanov (Union of pediatricians of Russia, 2020)
Acute gastroenteritis is an infectious disease, often with viral etiology, which can include diarrhea (three or more loose or liquid stools in 24 hours) and the possible presence of vomiting and fever. This pathology is common disease for any pediatrician in his practice. Currently, many specialists use a variety of different guidelines and approaches to the treatment of acute gastroenteritis, thus not all of them meet the criteria of evidence-based medicine. This review presents contemporary approaches to the pharmacotherapy of acute gastroenteritis based on world experience and guidelines from developed countries. This review also covers the issues of specific prevention of rotavirus infection and the role of vaccination in prevention of certain somatic diseases.